Predicting sharia commercial bank financial distress through financial liquidity ratio - Anissa Nurul Farohah; Dahruji Dahruji Dahruji (Indonesian Journal of Islamic Economics Research, 2023)
This study aims to predict the possibility of financial distress dominated by several liquidity ratios (Cash Ratio, Quick Ratio, and Current Ratio) at the Sharia General Bank in Indonesia. Researchers used logistics regression analysis research methodology. 12 Sharia General Bank registered with Bank Indonesia and Financial Services Authority in 2018, the first quarter to 2021, the fourth quarter used as a research sample. The results showed that the Cash Ratio, Quick Ratio, and Current Ratio had no negative effect on financial distress. With this research, researchers hope to provide an outline related to financial distress found by the Sharia General Bank and used as a focus on decision-making to address financial distress and minimize the occurrence of financial distress to address the problem.